Philosophical-Methodological Problems of Economics Project of Economic Phenomenology - Svoboda, Miroslav (2014)
In recent years, the economic approach to human behavior has been challenged by contributions of cognitive science. Thus two methodological strands in economics disagree with each other: the objectivistic approach favors the methods of natural science; the subjectivistic approach takes the teleological structure of human action as its cornerstone. It is argued that the position of the latter has been undermined and often degraded to a mere instrumentalist tool because it builds upon the primitive version of the teleological structure. Its deeper realist analysis is needed, which is the task for economic phenomenology: it identifies invariant pragmatic structures of human action, with various degrees of their anonymity. If the economic approach is founded on those structures adequately, then both rational choice theory and bounded rationality theories become compatible, as they differ in their degrees of anonymity only; they both belong to the body of the (subjectivistic) economic approach to human behavior. Economic phenomenology also offers a solution to the phenomenon of inconsistency of human action which is documented by cognitive sciences as a proof of human irrationality. The thesis shows that once the decision maker's description of the choice is allowed, inconsistency may disappear. Consistency is a matter of thinking, not acting. Therefore, a conceptual analysis of human thinking is needed. An example of the analysis is presented. It concentrates on the phenomenon of Self and works up the concept of the horizontality of Self. With this concept, inconsistency of human action is derived as a natural characteristic of our being-in-the-world. Inconsistency of human action is a pragmatic structure of human action, which even allows the decision maker some intentional control.